Aging of the Peritoneal Dialysis Membrane - Krediet, Raymond T. (Frontiers in Physiology, 2022)
Long-term peritoneal dialysis as currently performed, causes structural and functional alterations of the peritoneal dialysis membrane. This decay is brought about by the continuous exposure to commercially available glucose-based dialysis solutions. This review summarizes our knowledge on the peritoneum in the initial phase of PD, during the first two years and the alterations in function and morphology in long-term PD patients. The pseudohypoxia hypothesis is discussed and how this glucose-induced condition can explain all peritoneal alterations in long-term PD patients. Special attention is paid to the upregulation of hypoxia inducing factor-1 and the subsequent stimulation of the genes coding for glucose transporter-1 (GLUT-1) and the growth factors transforming growth factor-β (TGFβ), vascular endothelial growth factor (VEGF), plasminogen growth factor activator inhibitor-1 (PAI-1) and connective tissue growth factor (CTGF). It is argued that increased pseudohypoxia-induced expression of GLUT-1 in interstitial fibroblasts is the key factor in a vicious circle that augments ultrafiltration failure. The practical use of the protein transcripts of the upregulated growth factors in peritoneal dialysis effluent is considered. The available and developing options for prevention and treatment are examined. It is concluded that low glucose degradation products/neutral pH, bicarbonate buffered solutions with a combination of various osmotic agents all in low concentration, are currently the best achievable options, while other accompanying measures like the use of RAAS inhibitors and tamoxifen may be valuable. Emerging developments include the addition of alanyl glutamine to the dialysis solution and perhaps the use of nicotinamide mononucleotide, available as nutritional supplement.